The profile of an intuitive decision maker and the use of intuition in decision-making practice - Malewska Kamila (Management)
The profile of an intuitive decision maker and the use of intuition in decision-making practice The aim of this paper is to determine the relationship between the personality traits identified in the literature as characteristic of an intuitive decision-maker and the use of intuition in the decisionmaking process. In order to empirically verify this issue, the author conducted a pilot study. The article consists of three principal parts and is both theoretical and empirical in nature. The first part presents the essence of intuition and attempts to define this ambiguous concept. Next, the personality traits, abilities and predispositions which make up the profile of an intuitive decision maker are discussed. The final part of the paper is devoted to presenting the results obtained in the course of this empirical research.